Legal Legality of the Job Copyright Law After the Ruling of the Constitutional Court - Moh. Taufik; Iwan Setia Budi (Badan Penerbit STIEPARI Press, 2024)
The Constitutional Court program has decided that the Job Creation Law Number 11 of 2020 is conditionally unconstitutional, which in the legal considerations of the Constitutional Court's decision explains that the process of forming the Job Creation Law is contrary to the 1945 Constitution. This research aims toknow how the Constitutional Court decides on the Job Creation Law and understand the legal implications of the enactment of the Job Creation Law. This type of research uses library research. The approach used is normative juridical. Data collection techniques use library research. The results of this research show that there is a need to improve the Job Creation Law through amendments or the formation of new laws involving active and substantial public participation. Based on the results of this research, it is hoped that it will become information and input for students, academics, practitioners, and all parties in need within the Faculty of Law, Pancasakti University, Tegal.